Efektivitas Promosi Kesehatan melalui Metode Peer Education terhadap Pengetahuan dan Sikap Remaja tentang Bahaya Narkoba - Pannyiwi, Rahmat; Nurhaedah, Nurhaedah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Drug abuse is a serious public health problem, particularly among adolescents who are vulnerable to negative environmental influences. Health promotion using peer education is believed to increase knowledge and foster positive attitudes toward preventing drug abuse. This study aims to determine the effectiveness of health promotion using peer education on adolescents' knowledge and attitudes about the dangers of drugs. The study used a quasi-experimental design with a pretest-posttest control group design. The study population was high school students in a city in Indonesia, with a sample size of 60 students divided into intervention and control groups. The research instrument was a structured questionnaire that had been tested for validity and reliability. The results showed a significant increase in knowledge and attitudes in the intervention group after receiving health promotion using peer education (p < 0.05). The conclusion of this study is that health promotion using peer education is effective in increasing adolescents' knowledge and attitudes about the dangers of drugs. It is recommended that this program be implemented sustainably in schools to support drug abuse prevention efforts.